Patient preferences in in-patient psychiatry: structural elements for optimal care - Robert Davidson; Timur Liwinski; Rainer Gaupp; Lukas Imfeld; Annette B. Brühl; Marc Vogel; Christian G. Huber; Undine E. Lang (BJPsych Open, 2026)
Background The physical environment of psychiatric in-patient facilities plays a significant role in patient well-being, treatment satisfaction and recovery. Despite growing evidence that architectural design influences clinical outcomes, systematic data on patient preferences regarding hospital structure remain scarce. Aims To identify structural and architectural requirements for psychiatric hospital design, from the patient perspective. Method A cross-sectional, hybrid questionnaire survey incorporating closed- and open-ended questions was administered to former psychiatric in-patients from all wards of a tertiary care centre (University Psychiatric Clinics Basel, Switzerland) who had been treated before September 2023. The survey assessed patient-reported disturbances related to room conditions, preferences for structural and environmental design elements, importance ratings of specific architectural features (measured using Likert scales) and preferred treatment settings. Results A total of 604 participants completed the survey (response rate 19.1%). Room-related disturbances were reported by 49% of respondents ( n = 282), with key concerns including insufficient privacy, limited withdrawal opportunities and impaired sleep quality. Single-occupancy rooms were rated as very important (10/10) by 64% of respondents. Access to a surrounding park environment (74%) and direct outdoor access (75%) were among the most highly valued features. In-patient treatment was the preferred modality for 54.1% of respondents, followed by out-patient care (17.8%) and day clinics (15.9%). Conclusions Psychiatric patients strongly prioritise in-patient settings offering single-occupancy rooms, privacy and access to green spaces and outdoor areas. These findings underscore the importance of systematically incorporating patient perspectives into the architectural and structural planning of psychiatric facilities.